The art of city sketching : a field manual - Abrams, Michael (Michael C.) (New York : Routledge, 2021)
"The Art of City Sketching: A Field Manual guides readers through the process of free-hand architectural sketching and explains orthographic, diagrammatic, three-dimensional, and perceptual-type drawings. The book presents hundreds of drawings of historic buildings and urban spaces, examples, and exercises, which help readers develop their drawing skills and employ sketching as an analytical tool. The book is divided into three parts, based on reader's skill level: beginner, intermediate, and advanced. As an architect and field sketching instructor, the author shows that through drawing the reader can discover, analyze, and comprehend the built environment. The new edition of The Art of City Sketching expands on the drawing techniques of the previous version by adding new drawing examples, exercises, and two new chapters-- Chiaroscuro and Storyboard. New drawing tips, demonstrations, and composition "do's and don'ts" would support readers when they illustrate their viewpoint of the city by using simple drawing tools. The lessons in this book would allow those with beginners, intermediate, and advanced skills to mix method with imagination and sensibility"--
Includes bibliographical references and index.
Keywords: Architectural drawing -- Technique